Development and evaluation of an enzyme-linked immunosorbent assay (ELISA) for the determination of the trypanocidal drug homidium in serum of treated cattle - Murilla, G.; Eisler, M.C.; Peregrine, A.S.; Ndung'u, J.M.; Holmes, P.H. (Wiley, 1999)
Two enzyme-linked immunosorbent assays (ELISA) for the determination of homidium in serum of treated cattle have been developed and evaluated. One is a direct competition (Assay 1) and the other an indirect competition assay (Assay 2). Both assays are highly sensitive with a limit of detection of 0.1 ng homidium per mL serum. Homidium levels were measurable in serum of cattle for over 2 months following administration of a single intramuscular (i.m.) dose at 1 mg/kg bodyweight. The level of sensitivity afforded by these assays makes them potentially useful tools in the pharmacokinetic evaluation of homidium and for invetigating drug resistance or causes of drug failure. Assay 2 was chosen as being most suitable for further studies.